Hypoxic training for strength enhancement - Scott, B. R. (Hypoxia conditioning in health, exercise and sport: Principles, mechanisms and applications, 2025)
Physical activity guidelines recommend that adults incorporate resistance training on two days per week to improve or maintain muscle size and strength. This is important across the lifespan and for different populations. Healthy young athletes are typically prescribed resistance training to improve muscular strength and power specific to their chosen sport. This practice not only increases exercise economy and sporting performance but also reduces the risk of injury. Older adults should perform resistance training to attenuate age-related muscle mass loss, termed sarcophenia, and the reductions in functional abilities and independence that often accompany sarcophenia. Populations who experience chronic clinical conditions or are undertaking rehabilitation from an injury are also advised to undertake resistance training to help manage their diseases or accelerate recovery. To enhance the adaptations to resistance trainng, researchers have investigated the application of a hypoxic stimulus during this exercise. This was initially examined using a localized hypoxic stimulus by wearing inflatable cuffs on the arms or legs to limit blood flow (and therefore oxygen delivery) tot he limbs during exercise. Commonly referred to as blood flow restriction (BFR), this technique has been shown to substantially increase muscle size and strength when combined with low-load resistance training. However, the BFR stimulus is limited tot he muscles oft he limbs, and so researchers have also implemented systemic hypoxia ba having participants breathe hypoxic air during resistance training. Resistance training in hypoxia (RTH) has demonstrated augmentad muscular development in some studies, though these adaptations are not as consistently observed as for BFR training. This chapter provides an overview of these different hypoxic methods to enhance responses to resistance training, explaining the typical adaptations, proposed mechanisms, and practical implications of these techniques.